BEYOND THE MODEL: RETHINKING EDUCATION IN THE FACE OF DISABILITY PROTOTYPES - Fernandes, Kássia Lia Costa; Carvalho, Alanna Oliveira Pereira; de Souza, Paulo Vinicius Leite; Vieira-Neto, Antonio Eufrásio; Vieira, Natália Chaves Gondim; Lima Junior, Newton Sérgio; da Silva, Daniela Fialho; Paula, Nadja Ully Martins; de Arruda, Ítalo Rodrigo Paulino (Seven Editora, 2025)
This paper conducts a historical and social analysis of models of understanding disability and their relationship to the schooling process of the target audience for special education. Based on a literature review, we discuss the evolution of paradigms that have shaped social, medical, religious, and legal conceptions of disability. Our work explores the four main theoretical models of disability—religious, medical, social, and finally, biopsychosocial—evidencing how each influences educational practices and public policies aimed at people with disabilities (Oliveira, 2022). It is noteworthy that despite advances in legislation and fundamental rights, the realization of full inclusion still faces structural, attitudinal, and pedagogical barriers. Thus, overcoming these challenges requires a broader understanding of disability, combined with intersectoral policies and, of course, teacher training committed to equity and diversity. DOI: https://doi.org/10.56238/sevened2025.030-011